Ischemia: Nidogen‐1 Mitigates Ischemia and Promotes Tissue Survival and Regeneration (Adv. Sci. 4/2021). Issue 4 (17th February 2021) - Zbinden, Aline; Layland, Shannon L.; Urbanczyk, Max; Carvajal Berrio, Daniel A.; Marzi, Julia; Zauner, Monika; Hammerschmidt, Anne; Brauchle, Eva M.; Sudrow, Katrin; Fink, Simon; Templin, Markus; Liebscher, Simone; et al.
Abstract : In article number 2002500 by Katja Schenke‐Layland and co‐workers, the basement membrane protein Nidogen‐1 is shown to promote tissue survival and regeneration in ischemic conditions. Once thought as a simple linker protein, Nidogen‐1 increases heart function and decreases scaring in a myocardial infarction model, rescues pancreatic beta‐cell function in hypoxia, and modulates the immune system, demonstrating the multifaceted effect of Nidogen‐1.